Optimization of rebaudioside a extraction from Stevia Rebaudiana (Bertoni) and quantification by high perfomance liquid chromatography analysis - Asrul Afandi Ab. Halim; Shazani Sarijan; Ranajit Kumar Shaha (Universiti Malaysia Kelantan, 2013)
A solid-liquid extraction and an HPLC method for determination of rebaudioside A from the leave parts of Stevia rebaudiana were developed. Separation method consisted of solvent extraction of leaf powder using various solvents like petroleum ether, methanol, diethyl ether and butanol followed by its purification using high performance liquid chromatography in order to obtain bioactive compound rebaudioside A. This solvent selection is very important prior to alternative extraction methods since it can be used as a pre-extraction solvents, main solvents, or co-solvents. The problem of hydrolysable components and solvent removal difficulties in the conventional extraction led us to study further the effects of solvent properties on the conventional extraction using Soxhlet method in order to determine the best solvent or solvent mixture for high extraction yield of S. rebaudiana. The chromatographic separation was realized using a C18 column, mobile phase consisting of methanol: water with UV detection at 210 nm. Based on the yield of extraction and glycosides content, methanol was found to be best solvent.